(untitled) (Research, Society and Development, 2022)
The objective was to verify the difference in sleep quality and daytime sleepiness between university students with and without JLS. This is a field, descriptive, analytical, cross-sectional study carried out with 105 university students, selected by convenience. The JLS was measured by calculating the discrepancy between the times of sleeping and waking up on usual weekdays and weekends, individuals with an average sleep point >1 hour were classified as having JLS. The Pittsburgh Sleep Quality Index (PSQI) was used to analyze sleep quality and the Epworth Sleepiness Scale for daytime sleepiness. The JAMOVI statistical package was used, the comparison between the midpoints was performed using the paired t test, Comparison between sleep quality and daytime sleepiness scores among university students with and without JLS was performed using the independent t test, adopting an alpha of 0.05 in all analyses. The results indicate that JLS exists in about 1/3 of university students (38;36.2%). The data showed a statistically significant difference between the weekly midpoint and the weekend midpoint (p<0.001). Most college students (78; 74.3%) had poor sleep quality and levels of excessive daytime sleepiness (77; 73.3%). Independent t-test shows that college students with JLS have higher scores for poor sleep quality and excessive daytime sleepiness. It is concluded that college students with JLS have worse sleep quality and higher levels of excessive daytime sleepiness.